Rafflesia verrucosa (Rafflesiaceae), a new species of small-flowered Rafflesia from eastern Mindanao, Philippines - Balete, D. S.; Pelser, P. B.; Nickrent, D. L.; Barcelona, J. F. (Phytotaxa, 2014)
The new parasitic plant species Rafflesia verrucosa from Mt. Kampalili in eastern Mindanao (Philippines) is described, bringing the total number of Philippine Rafflesia to ten. Rafflesia verrucosa is the first small-flowered Rafflesia described from Mindanao Island, and differs notably from similar-sized species by the dense and prominently raised warts on the perigone lobes and diaphragm, the cup-shaped disk ornamented with dense pubescence on the abaxial surface, in the anther sulci and corona extending to the basal third of the disk exterior, the pleated, laminar and interconnected processes, the toroid annulus, and the extremely small and more numerous (20 or 21) anthers. Like R. baletei of Luzon, this new species has bisexual flowers. Rafflesia verrucosa is the third species found in the island of Mindanao where it occurs in montane forest from ca. 1300-1550 m., an exceptionally high elevation range for Philippine Rafflesia. It has the smallest flowers on average in the genus.